An in vitro study of mesiobuccal root thickness of maxillary first molars - dadresanfar, bahareh; Ravandoust, Yasaman; Najafi, Mohammad; Dadresanfar, Bahareh (Iranian Endodontic Journal, 2011)
Introduction: Understanding the internal anatomy of root canal system can significantly influence outcomes of root canal treatment. The aim of this in vitro study was to measure the thickness of mesiobuccal root at different levels in maxillary first molars. Materials and Methods: In this cross-sectional study, forty extracted human maxillary first molars were radiographed; accordingly, the mesial and distal root thicknesses of mesiobuccal (MB) roots were measured at four parallel horizontal levels. The samples were sectioned at the measured levels and then sections were scanned and saved in the computer. Buccal (B), Palatal (P), Mesial (M) and Distal (D) aspects of root thicknesses in single-canalled roots were measured. In two–canalled mesiobuccal roots, Distobuccal (DB) and Distopalatal (DP) aspects were evaluated alongside other measurements. Average radicular thickness in each aspect and each level was compared using ANOVA and t-test. Results: A total of 25 had two canals and 15 had one canal in MB root. In single-canalled roots M and D aspects were the thinnest whereas in two-canalled samples, the thicknesses of DP and DB aspects were significantly less than others (P<0.001). The B and P had the greatest thicknesses in all the samples. Conclusion: The results showed that special attention should be paid to "danger zone” areas of mesiobuccal maxillary first molar roots in order to avoid technical mishaps.